The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.susmat.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Activated carbon production by co-carbonization of feathers using water-soluble phenolic resin under controlled graphitization

Abstract: a b s t r a c tWe attempted to use feathers for the production of activated carbon (AC). A water-soluble resol-type phenolic resin was hybridized to prevent the liquefaction of the feathers and to control the graphitization degree of charcoal. The hybridization could effectively increase the yield of charcoal over 30% and maintained the graphitization degree at approximately 0.1, suitable for the production of AC. The Brunauer-Emmett-Teller (BET) surface area and the iodine-adsorption capacity of hybrid charco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The hybridization could effectively increase the yield of charcoal by over 30% and maintained the graphitization degree at approximately 0.1, suitable for the production of AC. They reported the production of materials with a surface area and iodine-adsorption capacity of 706 m 2 /g and 550 mg/g, respectively, almost twice as high in resin-free carbonized feather materials [255]. Kawahara also used similar systems to produce well-defined precursor fibres with nanoscale diameter for carbon nanofibers using electrospinning with resol-phenol formaldehyde resin, keratin and PVOH dissolved in water as the spinning dope.…”
Section: Phenol-formaldehyde Resinsmentioning
confidence: 99%
“…The hybridization could effectively increase the yield of charcoal by over 30% and maintained the graphitization degree at approximately 0.1, suitable for the production of AC. They reported the production of materials with a surface area and iodine-adsorption capacity of 706 m 2 /g and 550 mg/g, respectively, almost twice as high in resin-free carbonized feather materials [255]. Kawahara also used similar systems to produce well-defined precursor fibres with nanoscale diameter for carbon nanofibers using electrospinning with resol-phenol formaldehyde resin, keratin and PVOH dissolved in water as the spinning dope.…”
Section: Phenol-formaldehyde Resinsmentioning
confidence: 99%
“…However, original carbon fiber materials are relatively expensive to obtain, and this can become a limiting factor in the development of 3D carbon fiber–based structures on a large scale ( 10 ). Although hydrothermal treatment of diverse proteins usually induces their decomposition without forming carbonaceous materials ( 11 ), such structural fiber-based proteins as keratin ( 12 ) and collagen ( 13 ) as well as silk ( 14 , 15 ) have been reported as suitable for carbonization between 200° and 800°C, and in some cases even up to 2800°C ( 16 ). However, with the exception of some millimeter-scale silk nanofiber membranes ( 15 ) and up to 2-cm-large flexible carbonized silk worm cocoons ( 14 ), there are no reports on sponge-like and ready-to-use carbon scaffolds with hierarchical pores and 3D-connected skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of PVA-based charcoal at 800°C was no more than 5% [13]. Therefore, considering the composition of the cast film, the carbon yield exceeding 30% seems to be brought about by the co-carbonization effect between the w-ph and w-fk [8].…”
Section: Resultsmentioning
confidence: 94%
“…W-fk tends to self-assemble as the solvent water vaporizes [7]. Moreover, L-proline contained in w-fk will promote the carbonization of resolphenol formaldehyde resin through co-carbonization reactions [8], which is attractive when the as-electrospun fibers are converted into CNFs through carbonization. It was found that the spinning dope hybridizing w-fk to the amount of 30%, i.e.…”
Section: Resultsmentioning
confidence: 99%